2021
DOI: 10.1200/jco.2021.39.15_suppl.108
|View full text |Cite
|
Sign up to set email alerts
|

Finding the missing millions: Integrating automated viral hepatitis screening in a hospital with care and treatment in a primary care setting.

Abstract: 108 Background: Rates of hepatocellular carcinoma (HCC) are rising in the US. Patients at Saint Barnabas Medical Cancer Center (SBMC) present with late-stage HCC at higher rates (29%) compared to the national (16%). Chronic Hepatitis C (HCV) and Hepatitis B (HBV) are major drivers of liver cancer, yet screening rates are low. Finding these missing millions is important to reducing rates of HCC. An automated emergency department (ED) viral hepatitis (VH) screening program was initiated in 2018 at SBMC. In Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…HCV RNA results were available in two studies ( 37 , 39 ). Of 468 participants screened for anti-HCV, Fuster at al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV RNA results were available in two studies ( 37 , 39 ). Of 468 participants screened for anti-HCV, Fuster at al.…”
Section: Resultsmentioning
confidence: 99%
“…( 37 ) identified one participant positive for anti-HCV; HCV RNA was not detected in this anti-HCV positive individual using a Roche COBAS Real-Time PCR. In 25 participants positive for anti-HCV, Brogden et al ( 39 ) reported detectable HCV RNA in ten (40.0%) using Abbott Alinity m reverse transcription PCR.…”
Section: Resultsmentioning
confidence: 99%